HTLV-1 Infection and Cervicovaginal Susceptibility to High-Risk HPV: Findings from Women Living with HTLV-1 in Salvador, Brazil - Alisson de Aquino Firmino; Paulo Roberto Tavares Gomes Filho; Juliana Domett Siqueira; Luana Leandro Gois; Giselle Calasans de Souza Costa; Adenilda Lima Lopes Martins; Mariana Lima Drumond; Marcelo Alves Soares; Bernardo Galvão-Castro; Carlos Gustavo Régis da Silva; Maria Fernanda Rios Grassi (Viruses)
Persistent oncogenic HPV infection is strongly associated with cervical cancer. Studies have suggested a higher prevalence of HPV in women living with HTLV-1. This study aimed to determine whether HTLV-1 infection is associated with cervicovaginal HPV infection and to characterize HPV types according to oncogenic risk. Vaginal fluid samples were subjected to HPV diagnosis via PCR, and positive samples were subjected to Sanger sequencing and massive sequencing. Papanicolaou smears were examined using light microscopy to identify cell abnormalities. Among the 155 women screened, 79 were HTLV-1-infected and 76 were uninfected. HPV PCR identified 23 positive samples (15/79 vs. 8/76; p = 0.13). Twenty-three HPV types were identified, of which only types 31, 54, and 58 were present in both groups. When the number of HPV58 infections in each group was compared, women with HTLV-1 had a higher prevalence (8/79 versus 1/76; p = 0.03). In total, 61.9% of HTLV-1-infected women had at least one high-risk or probable high-risk HPV type (p = 0.12). Cytopathological findings were not significantly different between the groups. Further research is needed to determine whether HTLV-1 infection affects HPV progression and cervical cancer development and to assess the potential benefits of vaccination for women living with HTLV-1.